Motilitas Spermatozoa Ayam (Galus varius) Pada Penyimpanan Dingin Dengan Pengencer Tris, Cytrate, Kuning Telur, Filtrat Jambu Biji (Psidium guajava) Dan Buah Tin (Fikus karika rob) - Lukman H.Y.; Sumadiasya I.W.L.; Adji Santoso Dradjat (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2018)
The objectives of this study were to evaluate rooster semen preserved using Tris Citrate Egg Yolk-Citrate (TEYC) extender with the addition of Tin fruit and guava filtrate. Semen was collected by using plastic collector placed on cloaca, by using hen as a teaser when rooster mated hen consequently semen would remain in the plastic collector. Fresh semen was evaluated by evaluating volume, smell, color and spermatozoa concentration. Then semen was split into 7 fractions as treatment 1, 2 and 3 were extended 10 times using TEYC with 20%, 25% and 30% egg yolk. Then treatment 4 and 5 were extended using TEYC contain 20% egg yolk with 5 % and 10% guava filtrate. Treatments 6 and 7, were extended using TECY contain 20% egg yolk with Tin fruit filtrate of 5 and 10%. Then preserved and progressive motility was evaluated at 0, 12, 24 and 36 hours following chilling under 4°C. Results showed that ejaculate volume was 0.38 ± 0.14 ml, specific smell, milky white color with concentrations of 511.00 ± 90.07 x 107 sperms/ml. The results of progressive motility evaluation of 0, 12, 24 and 36 hours following chilling treatments 1 to 7 were not significantly different (P> 0,05). Percentage motility of chilling 0 hours and 36 hours of treatments 1 to 7, were from 86.50 ±4.72% to 48.83 ±5.15%, from 83.83 ±7.41% to 47.83 ±7.44%, from 88.67 ±1.86% to 49.33 ±9.35%, from 83.00 ±4.69 % to 43.50 ±7.77%, from 82.67 ± 6.06%, to 46.33 ±5.75%, from 83.83 ±7.41% to 47.83 ±7.44%, from 88.67 ±1.86% to 49.33 ±9.35% respectively and the average decreasing progressive motility up to 36 hours was 37.74 ± 1.64 %. Finally, it can be concluded that addition egg yolk, guava, and Tin fruit filtrate do not influence the progressive motility of local rooster spermatozoa.